Development of E-Modules with Sigil Software in Basic Women's Fashion Subjects Based on Entrepreneurship - Nur Ainiyah; Widiyanti; Didik Nurhadi; Achmad Romadin (Didaktika: Jurnal Kependidikan, 2024)
Currently digital modules (E-modules) are a solution for learning in the digital era. The aim of this research is to create an e-module that can provide knowledge and experience in fashion business management, and make basic women's fashion, analyze the feasibility level of e-module development and analyze the level of student response to the development product, namely an entrepreneurship-based basic women's fashion e-module. The method in this research is research and development, with the ADDIE development model. The product of this development is an entrepreneurship-based basic women's fashion e-module created with Sigil software, with data collection techniques, namely: unstructured interviews and closed questionnaires. The results of the trial on students obtained a response of 81%, in the very good category, namely students liked the layout of the e-module and the material presented was very relevant to their needs. And students feel satisfied and interested in studying the e-module. The result of the development is an e-module for making basic level women's clothing combined with entrepreneurial knowledge in the fashion sector. From the results of data analysis, it is concluded that this e-module can be used in madrasah aliyah plus fashion skills.